In situ-DRIFTS Study of Sb-V-CeO2/TiO2 Catalyst Under Standard and Fast NH3-SCR Conditions - Jeong, Young Eun; Kumar, Pullur Anil; Huong, Danh Thi; Ha, Heon Phil; Lee, Kwan-Young (SPRINGER/PLENUM PUBLISHERS, 2017)
In this study, the NOx conversion under standard and fast SCR conditions on the Sb-V-CeO2/TiO2 catalyst has been conducted in the temperature range of 150-400 degrees C. The Sb-V-CeO2/TiO2 catalyst, under both fast and standard NH3-SCR conditions, showed higher NOx conversion than the commercial V2O5/WO3-TiO2 catalyst at low temperatures. In comparison to the V2O5/WO3-TiO2 catalyst, the NO oxidation to NO2 was promoted for the Sb-V-CeO2/TiO2 catalyst at the temperatures between 150 and 400 degrees C. The in-situ DRIFTS studies at 200 degrees C on the Sb-V-CeO2/TiO2 catalyst surface indicated the IR bands assigned to NO2, nitrate species and ammonia adsorbed species assigned to Bronsted and Lewis acid sites under both standard and fast SCR conditions. Furthermore, in-situ DRIFTS results of Sb-V-CeO2/TiO2 catalyst revealed that the formation of surface adsorbed NO2, bridged nitrate and bidentate nitrate species. The reduction of nitrates to nitrites is induced by NO2, which reacts with the adsorbed ammonium species forming intermediate NH4NO2. Eventually, this is converted to N-2 and H2O in both SCR conditions.
Keywords: FAST SCR REACTION; LOW-TEMPERATURES; NITRIC-OXIDE; SO2 RESISTANCE; REDUCTION; NH3; NOX; AMMONIA; MECHANISM; ENHANCEMENT